Home » Simplify (frac{(2m – u)^2 – (m – 2u)^2}{5m^2 – 5u^2})

Simplify (frac{(2m – u)^2 – (m – 2u)^2}{5m^2 – 5u^2})

Simplify (frac{(2m – u)^2 – (m – 2u)^2}{5m^2 – 5u^2})
  • A.
    (frac{3}{5})
  • B.
    (frac{2}{5})
  • C.
    (frac{2m – u}{5m + u})
  • D.
    (frac{m – 2u}{m + 5u})
Correct Answer: Option A
Explanation

(frac{(2m – u)^2 – (m – 2u)^2}{5m^2 – 5u^2})
= (frac{2m – u + m – 2u)(2m – u – m + 2u)}{5(m + u)(m – u)})
= (frac{3(m – u)(m + u)}{5(m + u)(m – u)})
= (frac{3}{5})

Related:  If (4sin^2 x - 3 = 0), find the value of x, when 0° (leq)...